2021
DOI: 10.1080/1360144x.2021.1950725
|View full text |Cite
|
Sign up to set email alerts
|

Academic developers developing: aspects of an expanding lifeworld

Abstract: This text discusses the professional development of academic developers. It is based on the authors' reflections and observations in the context of a semi-formal programme, Strategic Academic Development, held for academic developers in different regions of the world. Most recently the programme participants were academic developers in Singapore. In this text, we as authors share what we notice as similar traits and common patterns across contexts when academic developers develop professionally and their 'life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Adding to the discussion of continuous scholarly development is faculty developers' identity. Mårtensson & Roxå (2021) posited that faculty developers' academic identity, primarily defined by their research and practice, is often ambiguous, one that is between two fields-their academic specialization and the field of faculty development. However, participant's responses did not show ambiguity of role in this study; all identified themselves as a facilitator or faculty member of the unit.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adding to the discussion of continuous scholarly development is faculty developers' identity. Mårtensson & Roxå (2021) posited that faculty developers' academic identity, primarily defined by their research and practice, is often ambiguous, one that is between two fields-their academic specialization and the field of faculty development. However, participant's responses did not show ambiguity of role in this study; all identified themselves as a facilitator or faculty member of the unit.…”
Section: Discussionmentioning
confidence: 99%
“…While developers' pedagogical knowledge and presentation skills are explicitly seen through PD events such as workshops and consultations, their own academic development is not often considered. Aspects such as continuous pedagogical learning, collegial relationships, and the individual developer's dual roles as both disciplinespecific academician and teaching and learning facilitator/ consultant (Mårtensson & Roxå, 2021) can significantly affect these educators and their communities. However, the faculty development community is not a common research focus as "there are comparatively fewer contributions on how we [academic developers] develop the knowledge and skills for the practice we engage in" (Mårtensson & Roxå, 2021, pp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this vein, the university's mission of teaching, research, and service should foster academic and social networks so that the speed of knowledge sharing, and exchange is increased (Elezi andBamber, 2018a, b, 2022;V at am anescu et al, 2018a). The university's management should highlight the benefits of knowledge sharing at different levels and stress the importance of online academic networks for academics to develop connections, to improve self-promotion or experience growth in their research and teaching activities, guaranteeing a constant flow of innovation, and shaping the respective university into a real learning organization (M artensson and Rox a, 2021).…”
Section: Literature Review and Hypotheses Development 21 Online Acade...mentioning
confidence: 99%